2017
DOI: 10.15406/mojap.2017.04.00130
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mice with Naringin Alleviates the Doxorubicin-Induced Oxidative Stress in the Liver of Swiss Albino Mice

Abstract: Doxorubicin a photosensitive antibiotic is frequently used to treat various malignancies in clinics; however, doxorubicin is also taken up by the normal cells of the body leading to increased oxidative stress and subsequently DNA damage and dysfunction in the cells. The agents which can reduce the adverse effect of doxorubicin will of great value. The present study has attempted to study the effect of naringin a citrus flavonoid on the doxorubicininduced oxidative stress in mice liver. The mice were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…32,56 The earlier studies on mice has also reported a decline in the GSH contents in the heart, liver and bone marrow cells. 24,33,34,57 Naringin treatment arrested the doxorubicin decline in the rat lung in the present study. Earlier naringin has been reported to alleviate the doxorubicin-induced decline in the GSH concentration in rat liver and mouse liver and bone marrow cells.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…32,56 The earlier studies on mice has also reported a decline in the GSH contents in the heart, liver and bone marrow cells. 24,33,34,57 Naringin treatment arrested the doxorubicin decline in the rat lung in the present study. Earlier naringin has been reported to alleviate the doxorubicin-induced decline in the GSH concentration in rat liver and mouse liver and bone marrow cells.…”
Section: Discussionsupporting
confidence: 51%
“…Earlier naringin has been reported to alleviate the doxorubicin-induced decline in the GSH concentration in rat liver and mouse liver and bone marrow cells. 24,33,34,58,59 The extract of Aegle mermelos has also been reported to increase the GSH contents in mice heart in an earlier study. 57 An amino acid glutamine has been also reported to protect rats against Doxorubicin-induced attrition in GSH contents.…”
Section: Discussionmentioning
confidence: 91%
“…The single injection (i.p) of DOX to mice results in significant depletion of antioxidants activity, which is in agreement with earlier reports from this laboratory in rat and mice liver 48,49 . Alleviation in GSH level might be due to its increased utilization by the hepatocytes in scavenging doxorubicin metabolites.…”
Section: Fig 9: Effects Of Aqueous Extract Of M Roxburghianus On Ansupporting
confidence: 92%
“…In the present study, a significant increase (61.97%) in MDA levels in liver cells was observed in DOX-treated animals. Similarly, DOX has been reported to increase lipid peroxidation in rat and mouse liver 48,49 . The increased LOO could be attributed to the overproduction of superoxide anion and reduction in detoxifying hyperperoxides.…”
Section: Fig 9: Effects Of Aqueous Extract Of M Roxburghianus On Anmentioning
confidence: 90%
See 1 more Smart Citation